Os mistérios do além no antigo Egipto : questões sobre a exploração museológica de um quadro conceptual - Sousa, Rogério (2008)
This article aims to point out the possibilities offered by a theoretical frame to the development of an exhibition plan. The «Mysteries of the Beyond in Ancient Egypt», the subject of the exhibition that took place in the Casa-Museu Teixeira Lopes from 26th February to the 26th of March of 2008, are here discussed from a theoretical point of view, in order to identify the guidelines that should have been present in the museological treatment of the Egyptian collection of Museu de História Natural da Universidade do Porto. The problems raised by the lack of scientific criteria adopted in the museological work are thus the main topic of our discussion.